Implementation of Aqidah Learning Through Inquiry Learning Strategies in Enhancing Students’ Religious Awareness - Ahmad Danil Tanjung; Rustam Ependi; Jamaluddin Jamaluddin (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2025)
This study aims to analyze the implementation of the Inquiry Learning strategy in Aqidah Akhlak instruction to enhance students’ religious awareness at Al-Manar Private Madrasah Aliyah (MAS). This study employs a qualitative approach with a descriptive research design. The research informants consisted of Aqidah Akhlak teachers, students, and the school principal or the vice principal in charge of the curriculum. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model developed by Miles, Huberman, and Saldaña through the stages of data reduction, data presentation, and drawing conclusions. Data validity was strengthened through triangulation of sources and techniques. The research results indicate that the Inquiry Learning strategy was implemented through the stages of orientation, problem formulation, hypothesis formulation, data collection, hypothesis testing, and drawing conclusions. The implementation of this strategy fostered active engagement, critical thinking skills, independent learning, and a deeper understanding of religious values. Increased religious awareness was reflected in discipline in performing religious duties, participation in religious activities, improved moral character, strengthened faith, and the ability to apply Islamic values in daily life.